Analysis of the dependence of survival in patients with gastric cancer on the location and characteristics of the tumor - O. M. Levyk; K. V. Barannikov (Zaporozhye State Medical University, 2013)
Introduction In Ukraine the rate of gastric cancer is 23 cases per 100 thousand of population. Despite the stable decrease in morbidity and mortality, this pathology continues to be in the top five most common malignancies among men and in the top six among women. The high prevalence of the disease influenced the need to find factors predicting survival of patients with gastric cancer. Recently, the degree of differentiation and depth of invasion of the primary tumor are often used for prognosis. In recent years, there was interest in the study of survival of patients depending on the location of gastric cancer. Some authors, such as N.A. Shanazarov and D.T. Arybzhanov (2009) stated that badly results of treatment are in patients with cancer of the cardiac part of stomach. In cancer of the lower third of the stomach, they discovered a two-year survival rate from 82.9 % to 67.5 %. The survival rate for cancer of the stomach body (middle third) ranged from 69.1 % to 57.9 %. Researchers noted the lowest three-year survival rate in the subtotal and total gastric cancers. Object Study and analysis of the dependence of survival in patients with gastric cancer stages I-IV on the location and characteristics of the tumor. Materials and methods 293 case histories of patients with gastric cancer stages I-IV, operated in Zaporozhye Regional Clinical Oncology Dispensary during the period from August 2000 till May 2012 were studied. Among them there were 190 men (64.8 %), and 103 women (35.2 %). Patients with gastric cancer with tumor in the pyloric part of stomach - 102 (34.8 %), in the body of stomach - 139 (47.4 %), proximal part - 36 (12.3 %) and patients with total gastric tumor lesions - 16 patients (5.5 %) - were included into study. In addition to location of the tumor in the stomach data on such characteristics of malignant tumors as the degree of differentiation and histological structure of the tumor have been analyzed. Among patients with gastric cancer, 14 patients (4.8 %) had well differentiated tumors (G1), 23 patients (7.8 %) - moderately differentiated (G2), 165 patients (56.7 %) - poorly differentiated (G3) and undifferentiated cancer (G4) - 91 patients (31.1 %). The histological structure of stomach cancer was studied.There were 197 patients with adenocarcinoma of the stomach (67.2 %), a group of patients with undifferentiated tumors - 96 (32.8 %). Results and Discussion In the study of survival of patients according to the tumor in the stomach we have found the best survival rates in patients with gastric cancer localized in pyloric part compared with localization in the proximal part or the body of stomach (median survival rates were respectively 60.4 months, 55.1 month and 47.1 months). The worst survival rate was observed in patients with a total spread of malignant tumors in the stomach, the median survival was only 14.9 months. Analysis of observation of patients with gastric cancer of various differentiation degrees showed a difference in survival rates. When comparing the group of patients with moderately differentiated tumors with patients with poorly differentiated tumors difference in survival rates is small and only 7.8 months (median survival rates are 53.2 and 45.4 months). But when comparing moderately differentiated tumors we found a significant difference. The median survival of patients with undifferentiated carcinoma is only 33 months. Conclusions 1. Tumor in patients with gastric cancer stages I-IV does not affect their survival (p = 0, 12). Yet, patients with gastric cancer, with a primary tumor in the pyloric part have the best survival rate of 60.4 months. 2. Simplification of tumor differentiation does not lead to a deterioration in the prognosis of patients with gastric cancer stages I-IV (p = 0,19).